Tunable Negative Differential Resistance in SnO2:Co Memristors on p-Si - Jamoliddin X. Murodov; Shavkat U. Yuldashev; Azamat O. Arslanov; Marguba S. Mirkamilova; Utkur E. Jurayev (East European Journal of Physics)
This study investigates the negative differential resistance (NDR) phenomenon in cobalt-doped tin dioxide (SnO2:Co) memristors fabricated on p-type silicon substrates. Using ultrasonic spray pyrolysis (USP), crystalline SnO2:Co thin films were deposited on p-Si substrates with a thin native SiO2 layer. The resulting memristor devices exhibit reproducible bipolar resistive switching between high-resistance (HRS) and low-resistance states (LRS). Key findings include the observation of a distinct NDR region in the current-voltage (I-V) characteristics, specifically in the positive voltage range from approximately +3V to +4V. Within this NDR region, current decreases despite increasing voltage, a characteristic hallmark of this effect. This behavior is attributed to the charge trapping and redistribution within the Co:SnO2 material. The consistent and reproducible nature of the observed NDR effect suggests the potential of SnO2:Co memristors for applications in advanced memory and switching technologies. This work contributes to the understanding of resistive switching mechanisms in Co-doped SnO2 thin films, which are promising materials for next-generation memory devices.